Susceptibility Genes and HLA for Cold Medicine-Related SJS/TEN with SOC - Ueta, Mayumi (Frontiers in Genetics, 2022)
We investigated the genetic predisposition for- and the pathogenesis of Stevens-Johnson syndrome/epidermal necrolysis with severe ocular complications (SJS/TEN with SOC). Cold medicines (CMs) including multi-ingredient cold-medications and non-steroidal anti-inflammatory drugs (NSAIDs) were implicated in the development of SJS/TEN with SOC. Studies of the association between HLA genotypes and CM related SJS/TEN with SOC (CM-SJS/TEN with SOC) revealed an association with HLA-A*02:06 in the Japanese; it may be a marker in Koreans. HLA-B*44:03 was associated in the Japanese, in Thais, in Indian; in Brazilians of European ancestry it may be a positive marker. PTGER3 is a susceptibility gene; HLA-A*02:06 and PTGER3 polymorphisms exerted additive effects in Japanese and Korean patients. A genome-wide association study showed that IKZF1 was associated in the Japanese. A meta-analysis including Japanese, Koreans, Indians, and Brazilians also revealed an association between CM-SJS/TEN with SOC and IKZF1. The up-regulation of hsa-miR-628-3p in the plasma of SJS/TEN with SOC patients may suppress the expression of TLR3 and of innate immune-related genes. Not only CMs, but also the interaction of TLR3, PTGER3, IKZF1 and HLA, and maybe some microbial infections are necessary for the onset of SJS/TEN with SOC.